A New Compact CMOS Realization of Sinusoidal Oscillator Using a Single Modified CBTA - Herencsar, Norbert; Koton, Faroslav; Vrba, Kamil; Lahiri, Abhirup; Ayten, Umut E.; Sagbas, Mehmet (BRUNO UNIV TECHNOL, DEPT RADIO ELECTRONICS, 2011)
In this paper, a new compact realization of sinusoidal oscillator using modified current backward transconductance amplifier (MCBTA) is reported. The proposed circuit employs a single MCBTA and four passive components including two grounded capacitors. The circuit provides completely de-coupled condition of oscillation (CO) of the frequency of oscillation (FO), i.e. no term in the CO is present in the FO and vice versa. Both the CO and FO are independently tunable by two different grounded resistors. The FO is also tunable by means of the transconductance and thereby is electronically tunable. SPICE simulation results have confirmed the workability of the proposed circuit.
Keywords: Analog circuits; sinusoidal oscillator; MCBTA; Engineering; Telecommunications